2016
DOI: 10.1186/s12981-016-0113-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Tenofovir on renal function among Ugandan adults on long-term antiretroviral therapy: a cross-sectional enrolment analysis

Abstract: BackgroundWHO recommends using Tenofovir containing first line antiretroviral therapy (ART), however, Tenofovir has been reported to be associated with renal impairment and dysfunction. We compared renal function among individuals on Tenofovir and those on non-Tenofovir containing ART.MethodsIn a cross-sectional study of HIV-Positive adults on ART, at enrolment into a prospective cohort to study the long-term complications of ART in Uganda, information on biophysical measurements, medical history, clinical exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…Although most patients who were on protease inhibitor plus NRTI received tenofovir-containing regimens and we used sparse renal toxicity monitoring (achievable in typical programme settings), few patients developed clinically significant renal toxicity. This finding is consistent with reports from similar African programme settings, 16 , 17 and shows that intensive renal monitoring is unnecessary in the public health approach in Africa, even in second-line therapy in which serum concentrations of tenofovir are boosted by concomitant protease inhibitor use. More data are needed in Asian patients in whom lower average bodyweight might further increase tenofovir concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…Although most patients who were on protease inhibitor plus NRTI received tenofovir-containing regimens and we used sparse renal toxicity monitoring (achievable in typical programme settings), few patients developed clinically significant renal toxicity. This finding is consistent with reports from similar African programme settings, 16 , 17 and shows that intensive renal monitoring is unnecessary in the public health approach in Africa, even in second-line therapy in which serum concentrations of tenofovir are boosted by concomitant protease inhibitor use. More data are needed in Asian patients in whom lower average bodyweight might further increase tenofovir concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, as opposed to TDF nephrotoxicity, the serum phosphate level was higher in TDF based regimen compared to non-TDF based regimen after 12 months of ART. Although larger retrospective cohort studies reported decline in kidney function with TDF use in Africa [ 21 23 ], there are also studies that showed no significant association of TDF use with renal impairment [ 41 , 46 , 47 ]. The different results and reports on renal safety of TDF in various populations may suggest that TDF associated kidney injury may be developing in genetically predisposed populations.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies undertaken in South Africa, Zambia, Uganda and Tanzania found no difference in the renal function of TDF exposed patients compared with TDF unexposed cohorts. 20,25,33,34 De Waal et al in a study of over 15,000 patients followed up for a median duration of 51 weeks reported an improvement on the kidney function of TDF treated patients that had mild renal dysfunction (<90 mL/min/1.73 sqm) at baseline. 20 The reasons for this difference may be attributed to the demographic and baseline clinical characteristics of the study population, as well as follow-up time.…”
Section: Cumulative Incidence Of Renal Impairment In the Study Populamentioning
confidence: 99%